Efficacy of case method learning in general practice for secondary prevention in patients with coronary artery disease: randomised controlled study. Issue 7369 (19th October 2002) - Kiessling, Anna; Henriksson, Peter
Abstract: Objective: To study the efficacy of case method learning, for general practitioners, on patients' lipid concentrations in the secondary prevention of coronary artery disease. Design: Prospective controlled trial. Setting: Södertälje, Stockholm County, Sweden. Participants: 255 consecutive patients with coronary artery disease. Intervention: Guidelines were mailed to all general practitioners (n=54) and presented at a common lecture. General practitioners who were randomised to the intervention group participated in recurrent case method learning dialogues at their primary healthcare centres during a two year period. A locally well known cardiologist served as a facilitator. Main outcome measure: Concentration of low density lipoprotein cholesterol at baseline and after two years. Analysis according to intention to treat (intervention and control groups (n=88)) was based on group affiliation at baseline. Results: Low density lipoprotein cholesterol was reduced by 0.5 mmol/l (95% confidence interval 0.2 to 0.8 mmol/l) (9.3% (2.9% to 15.8%)) from baseline in patients in the intervention group and by 0.5 (0.1 to 0.9) mmol/l compared with controls (P<0.05). No change occurred in the control group (0.0 (−0.2 to 0.2) mmol/l). Low density lipoprotein cholesterol decreased by 0.6 (0.4 to 0.8) mmol/l in a group of patients who received specialist care. Conclusion: Case method learning resulted in a lowering of low density lipoprotein cholesterol in the primary care patients with coronary artery disease comparable to that achieved at a specialist clinic. Conventional presentation of practice guidelines had no effect.